A unique case of polymorphism in polyiodide networks resulting from the reaction of the drug methimazole and I2. (11th April 2023) - Aragoni, M. Carla; Arca, Massimiliano; Demartin, Francesco; Garau, Alessandra; Isaia, Francesco; Lippolis, Vito; Pivetta, Tiziana
Abstract : The oxidation of methimazole (C4 H6 N2 S) by I2 in H2 O yielded the ionic compound [2(C4 H5 N2 S–SN2 C4 H6 )]I3 I5 (1 ) in 1-triclinic and 1-monoclinic polymorphs. Abstract : The oxidation of thioamide methimazole (C4 H6 N2 S) with molecular diiodine in water afforded the ionic compound [2(C4 H5 N2 S–SN2 C4 H6 )]I3 I5 (1 ) in 1-triclinic and 1-monoclinic polymorphs. The polymorphic nature of [C4 H5 N2 S–SN2 C4 H6 ]2 I3 I5 has been highlighted by comparing the structure of the 1-triclinic form with that of the 1-monoclinic form reported in the literature. No significant geometric differences are observed for the cations in the two polymorphs. The polymorphism is essentially due to a different arrangement in the polyiodide network of the [I5 ] − and [I3 ] − components. The FT-Raman spectrum of 1-triclinic shows the characteristic bands in the range 200–50 cm −1 which are in good agreement with the structural features of the polyiodide network. The molecular electrostatic potential maps of the cation methimazole-disulfide [C4 H5 N2 S–SN2 C4 H6 ] + and the bis-cation methimazole-disulfide {[C4 H5 N2 S–SN2 C4 H6 ] + }2 in 1-triclinic have been studied to clearly identify the electrostatic potential energy distributions over the cations, and the electron belt and σ-hole areas responsible for the directionality of the non-covalent interactions in the polyiodides. It is suggested that the cation methimazole-disulfide may be a reaction intermediate in the inhibition of thyroid hormones by methimazole.